Upaya Peningkatan Kompetensi Profesional Guru melalui Pelatihan Media Pembelajaran Digital - All Fine Loretha; Wakhid Fitri Albar (Universitas Negeri Semarang, 2023)
Covid-19 is a pandemic experienced by almost the entire world. The pandemic caused significant changes in various fields, including education. The pandemic policy that made schools switch from face-to-face to virtual meetings created new problems for educators. Teachers need more time to be ready to face the changes that occur. Previously, learning during a pandemic only focused on giving homework, which was then collected via photos in the WhatsApp group. This makes learning less interactive and conducive. This community service prepares elementary school teachers to develop digital learning media. So that learning activities during a pandemic can be resolved. The community service method uses adult training methods. The service participants totaled 30 people who were teachers at the Integrated Bhaskara Subang Islamic Elementary School. As a result of this community service, teachers can create Canva-based interactive PowerPoint learning media, which can be boldly implemented by online. This increases the professional competence of elementary teachers in learning during a pandemic.